2022
DOI: 10.3390/su14116744
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Effect of an Entrepreneurial Environment on College Students’ Entrepreneurial Self-Efficacy: The Mediating Effect of Entrepreneurial Competence and Moderating Effect of Entrepreneurial Education

Abstract: Background: entrepreneurial self-efficacy is the level of confidence that entrepreneurs can complete various entrepreneurial tasks. It can significantly predict entrepreneurial effectiveness, entrepreneurial motivation and entrepreneurial ability. This study explores the mechanism of entrepreneurial environment on college students’ entrepreneurial self-efficacy and analyzes the role of entrepreneurial competence and entrepreneurial education in the relationship between entrepreneurial competence and entreprene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 32 publications
3
15
0
1
Order By: Relevance
“…The results confirmed that the campus learning environment mediated the relationship between the entrepreneurial curriculum (curriculum content, curriculum material, teaching strategies, and feedback and assessment) and entrepreneurial competencies, which approved our hypotheses H4a-H4d. These findings are in line with past research conducted on exploring the mediating effect of the entrepreneurial education on entrepreneurial attitudes (Barnes and de Villiers Scheepers, 2018;Lu et al, 2021;Luo et al, 2022;Valencia-Arias et al, 2022). Furthermore, Choi and Markham (2019) discussed the significance of the campus learning environment role to develop entrepreneurial competencies among the students as per the need of industry.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The results confirmed that the campus learning environment mediated the relationship between the entrepreneurial curriculum (curriculum content, curriculum material, teaching strategies, and feedback and assessment) and entrepreneurial competencies, which approved our hypotheses H4a-H4d. These findings are in line with past research conducted on exploring the mediating effect of the entrepreneurial education on entrepreneurial attitudes (Barnes and de Villiers Scheepers, 2018;Lu et al, 2021;Luo et al, 2022;Valencia-Arias et al, 2022). Furthermore, Choi and Markham (2019) discussed the significance of the campus learning environment role to develop entrepreneurial competencies among the students as per the need of industry.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, researchers have also explored the mediating role of the campus learning environment in the relationship between the entrepreneurial curriculum and entrepreneurial competencies. Luo et al (2022) conducted a study with 1,100 students in Guangdong, China, and found that the entrepreneurial environment is "the basis for the entrepreneurial project execution and can provide sufficient external conditions for the entrepreneurial activity implementation and concluded that a positive entrepreneurial environment can provide rich resources to support entrepreneurial activities and meet the elemental conditions required for the development of entrepreneurial projects." Furthermore, Valencia-Arias et al (2022) found that university environments equipped with tools that facilitate training and the development of entrepreneurial skills using different types of resources allow students to have better attitudes toward entrepreneurship.…”
Section: Mediation Effect Of Campus Learning Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Emotion originates from meaning. Social capital can strengthen the process of meaning construction (Bullough and Renko, 2013 ; Luo et al, 2022 ). The Passion comes from the explicit and implicit contract relationship between the entrepreneur and the external environment, which is also embodied in the “Root.” The more external contracts the entrepreneur has, the more diversified the roles he assumes.…”
Section: Theoretical Basis and Hypothesismentioning
confidence: 99%
“…Una cuestión importante en las mismas dimensiones que las anteriores, es sobre la cultura, factor clave que determina el éxito o fracaso del emprendimiento (Useche, Giler y Guerrero, 2019; Barbetti, 2020;Cantillo et al, 2021;Luo et al, 2022), de ella dependerá si la población emprendedora, para el presente caso, los estudiantes, alcancen tanto el diseño como su implantación con criterios de eficiencia y sostenibilidad en el tiempo. Por tanto, los resultados alcanzados en la presente investigación, se acercan a aquellos que fueron abordados considerando los elementos de análisis.…”
Section: Tabla 3 Importancia De Una Cultura Emprendedoraunclassified